Ethnomedicinal plants used for treatment of snakebites in Tanzania - a systematic review - Neema Gideon Mogha; Olivia John Kalokora; Halima Mvungi Amir; David Sylvester Kacholi (Taylor & Francis Group, 2022)
Context Snake envenomation is one of the neglected health problems in Tanzania. Since most people, especially in rural areas, suffer from its burden, their cases are not documented due to reliance on medicinal plants. Despite the pivotal role of medicinal plants in treating snakebites, there is a paucity of information.Objective This review documents medicinal plants used to treat snakebites in Tanzania.Materials and methods A systematic search using electronic databases such as PubMed, Google Scholar, Scopus, Science Direct and grey literature was conducted to retrieve relevant information on medicinal plants used to treat snakebites in Tanzania. The review was conducted as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The obtained information from 19 published articles was organized and analysed based on citation frequency.Results A total of 109 plant species belonging to 49 families are used as snakebite antivenom in Tanzania. Fabaceae had the highest number of medicinal plants (19.3%). The dominant plant growth forms were trees (35%) and shrubs (33%). Roots were the most frequently used plant part (54%), followed by leaves (26%) and bark (11%). Annona senegalensis Pers. (Annonaceae), Dichrostachys cinerea (L.) (Fabaceae), Suregada zanzibariensis Baill. (Euphorbiaceae), Antidesma venosum E.Mey. ex Tul. (Phyllanthaceae), Cissampelos pareira L. (Menispermaceae) and Dalbergia melanoxylon Guill. & Perr. (Fabaceae) were the most cited medicinal plants.Conclusions Tanzania has diverse plants used for snakebite treatment; a few have been analysed for their bioactive components. Further study of the phytochemicals may provide scientific information to develop snakebite drugs.